Social Media Use, Work Environment and Research Output of Lecturers in Private Universities in Ogun State, Nigeria - Adebowale Adetayo (MO.RI Publishing, 2023)
This study examined the relationship between social media (SN) use, work environment (WE), and research output among lecturers in private universities in Ogun State, Nigeria. A survey research design was utilized, with a sample population of 621 lecturers from management & social science and natural & applied science in all private universities in Ogun State. Data was collected using a questionnaire, and both descriptive and inferential statistics were used to analyze the data. The findings showed that the level of output among lecturers was low, with a higher preference for publishing journal articles over other types of publications such as books and seminar papers. The extent of SN use among lecturers was found to be below average, while the quality of WE were found to be conducive for research activities. The study also revealed that SN and WE jointly influenced lecturers' research output. In conclusion, this study recommends that lecturers increase their use of SN while at the same time ensuring a conducive work environment to improve the low research output among lecturers in private universities in Ogun State, Nigeria. The combined use of SN and a supportive WE could enhance research output and contribute to the overall academic success of lecturers in private universities.